Nudos - Farah, Nuruddin, 1945- (Nuevos tiempos (Madrid, Spain), 2013)
Set in Mogadiscio, Somalia, this novel breaks new ground and brings the author back to his literary roots. He presents the story of a woman raised in North America who returns to her homeland in a desperate attempt to find herself and reclaim her family's home from the warlord who has taken it.